2007
DOI: 10.1097/gim.0b013e3180986e05
|View full text |Cite
|
Sign up to set email alerts
|

The use of anterolateral bowing of the lower leg in the diagnostic criteria for neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 is diagnosed clinically based on the presence of two of seven criteria developed by a panel of experts in 1987. The sixth criterion focuses on skeletal findings and is as follows: "A distinctive osseous lesion such as sphenoid dysplasia or thinning of long bone cortex, with or without pseudarthrosis." The wording for this criterion is misleading. In particular, "thinning of long bone cortex" is not the characteristic radiographic presentation, and no mention of long bone bowing is incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…Based on our previous clinical experience, NF1 individuals with anterolateral bowing of the lower leg prior to fracture have medullary canal narrowing with cortical thickening 6. Our retrospective radiographic review confirmed the appearance of cortical thickening with medullary canal narrowing near the apex of the bowing most consistently located near the junction of the middle and distal thirds of the tibia on plain films.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Based on our previous clinical experience, NF1 individuals with anterolateral bowing of the lower leg prior to fracture have medullary canal narrowing with cortical thickening 6. Our retrospective radiographic review confirmed the appearance of cortical thickening with medullary canal narrowing near the apex of the bowing most consistently located near the junction of the middle and distal thirds of the tibia on plain films.…”
Section: Discussionsupporting
confidence: 64%
“…The NF1 diagnostic criterion for the skeletal abnormalities states: “A distinctive osseous lesion such as sphenoid dysplasia or thinning of long bone cortex, with or without pseudarthrosis.”2,3 Our anecdotal clinical experience is that cortical thinning was not a consistent component of tibial dysplasia in NF1 6. This prompted us to systematically investigate our clinical suspicions and better characterize the geometry of the tibia and fibula in individuals with NF1 with anterolateral bowing of the lower leg.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of reported children have been born into known HNPCC families. As a result of their studies of long bone dysplasias in NF1 Stevenson et al [33] have recently suggested alteration to the wording of criterion 6 of the NIH criteria and I have included this in the revised criteria (table 3).…”
Section: Nf1 Diagnostic Criteriamentioning
confidence: 97%
“…Other osseous abnormalities are also observed and include short stature for familial background, bone overgrowth, bone cysts, increased dental caries, osteopenia, and non-dystrophic scoliosis. The skeletal abnormalities are a key component in the clinical diagnosis of individuals with NF1 [6–8], and skeletal abnormalities taken as a whole are quite common in NF1 [5]. …”
Section: Introductionmentioning
confidence: 99%